THE RELATIONSHIP BETWEEN SOCIAL SUPPORT FROM PEERS AND FAMILY AND THE QUARTER LIFE CRISIS IN K-POP FANDOM - Afiyah, Fairuzi; Hazim, Hazim (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the relationship between peer and family social support and the quarter life crisis experienced by individuals within the K-pop fandom, specifically members of the Seventeen (Carat) fan community. Method: Using a quantitative correlational design, data were collected from 146 purposively selected participants out of a population of 250 fandom members. The analysis employed a multiple regression correlation test to assess the influence of social support on the quarter life crisis. Results: The findings indicate a significant negative relationship between peer social support and quarter life crisis (r = -0.385; p < .001), and between family social support and quarter life crisis (r = -0.445; p < .001). The combined contribution of peer and family social support to the reduction of quarter life crisis was 56.5%, suggesting that greater perceived support is associated with lower levels of psychological distress during emerging adulthood. Novelty: This research introduces a unique perspective by focusing on the psychosocial dynamics of the K-pop fandom—particularly the Seventeen fandom—which remains an underexplored population in psychological studies. The findings contribute to the growing discourse on youth mental health in digital fan communities, emphasizing the protective role of social support.